Ischemic Conditioning Attenuates Platelet-Mediated Thrombosis: A Tale of Reverse Translation. (September 2017) - Przyklenk, Karin; Whittaker, Peter
Data obtained in both preclinical models and humans have revealed that the favorable cardiac consequences of ischemic conditioning extend beyond a direct effect on the cardiomyocyte. In the current review, we summarize our as-yet limited understanding of the complex relationships between ischemic conditioning, platelet activation–aggregation, and cardioprotection.